Surface Modification of the Aramid Fibers to Improve Adhesion to Epoxidised Natural Rubber: A Model Composites - Ahmad, Ishak; Siew Chin, Tan; Abdullah, Ibrahim (Malaysian Journal of Science, 2003)
Adhesion between aramid fibers and epoxidised natural rubber (ENR) was measured, in droplet form, using the microbond pull-out method. Both untreated (HM) and treated with a special epoxy-based adhesion-activating finish (HMA) aramid fibers were dipped in resorcinol formaldehyde latex (RFL) and bonded to ENR matrix. The shape of the droplets was determined by optical microscopy. The interfacial shear strength of the fiber/matrix bond was tested using a microvise grip in a tensile strength tester. It has found that both HM and HMA fibers treated with RFL had higher interfacial shear strength compared to the fibers without RFL. This behaviour was supported by scanning electron microscope analysis of the specimens following pull-out testing. The results led to the conclusion that both epoxy-based adhesion activation and RFL coated fiber increase the interfacial adhesion between the aramid fiber and ENR matrix.